(untitled) (Research, Society and Development, 2022)
Objective: To analyze the correlation between vector control indices, climatic variables and incidence coefficients of dengue, zika and chikungunya in the city of Ribeirão Preto, SP. Method: Ecological study, with data obtained from the Information System on Notifiable Diseases, Environmental Surveillance and the page of the Integrated Center for Agrometeorological Information. Data were analyzed using Spearman’s correlation (ρ) and generalized linear model with negative Binomial distribution and identity link function. Results: Temperature had a positive relationship with the coefficient of dengue incidence, p<0.01, with each degree of temperature increase increasing by 19.2 cases per 100,000 inhabitants. Conclusion: The study found no correlation between the Breateau indices, building infestation and type of container and the incidence of these arboviruses; however, there was a positive relationship between temperature and the incidence of dengue.